Interview and tribute to Maria Adélia Aparecida de Souza. Debating Brazilian Geography - Costa, Everaldo Batista (2024)
This interview is part of vol. 8, no. 15 of PatryTer - Latin American and Caribbean Journal of Geography and Humanities, which pays tribute to Maria Adélia Aparecida de Souza, Full Professor of the Department of Geography at the University of São Paulo (USP) who has dedicated herself to Brazilian Geography for over sixty years. Thus, by presenting this interview, we are continuing with one of the projects or objectives that accompany our journal, which includes paying tribute to the main figures in Geography and other social sciences from and for Latin America.